A self-immobilizing near-infrared fluorogenic probe for sensitive imaging of extracellular enzyme activity in vivo - Li, Yuyao (Royal Society of Chemistry, 2020)

(untitled) (Chem Sci)
Reported herein is a self-immobilizing near-infrared fluorogenic probe that can be used to image extracellular enzyme activity in vivo. Using a fluorophore as a quinone methide precursor, this probe covalently anchors at sites of activation and greatly enhances the fluorescence intensity at 710 nm upon enzymatic stimulus, significantly boosting detection sensitivity in a highly dynamic in vivo system.